4.7(2f - 0.5) = -6(1.6f-8.3f)

Put answer in exact value form.

### 1 Answer | Add Yours

Solve 4.7(2f-0.5)=-6(1.6f-8.3f):

4.7(2f-0.5)=-6(1.6f-8.3f) Add the like terms in the parantheses

4.7(2f-0.5)=-6(-6.7f) Use the distributive property to eliminate parantheses

9.4f-2.35=40.2f Subtract 9.4f from both sides

-2.35=30.8f Use the symmetric property

30.8f=-2.35 Divide both sides by 30.8

`f=-47/616`

----------------------------------------------------------

The solution is `f=-47/616`

---------------------------------------------------------

Check:

left side: `4.7(2(-47/616)-0.5)=4.7(-94/616-308/616)`

`=4.7(-201/308)=-9447/3080`

right side: `-6(1.6(-47/616)-8.3(-47/616))=-6(-47/385+3901/6160)`

`=-6(3149/6160)=-9447/3080` as required.

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes